PRESERVATION OF NATIONAL ART HERITAGE AND ITS IMPLEMENTATION IN THE EDUCATIONAL PROCESS - Oripova Malika Abdutolib qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the methods and strategies for preserving national art heritage and integrating it into the educational process. National art heritage reflects a nation’s cultural identity, historical experience, and aesthetic values. Its inclusion in educational practices contributes to the development of students’ artistic competence, creativity, and cultural awareness. The study examines pedagogical approaches, teaching methods, and practical activities that ensure the effective transmission of traditional art knowledge to learners, fostering respect for cultural heritage and promoting aesthetic and creative skills in educational settings.